Enhanced sequence detector in the presence of intersymbol interference and non-Gaussian noise - Chuah, , TC (2004)
A new Viterbi equaliser is proposed for joint mitigation of intersymbol interference and impulsive noise. The new equaliser uses a robust branch metric incorporating the Talwar penalty function. It is shown that the proposed equaliser facilitates considerable performance improvements.